The Dragon and the Eagle: Reforming China’s Securities IPO Laws in the U.S. Model, Pros and Cons - Stuart R. Cohn; Miao Yinzhi (Washington University Global Studies Law Review, 2018)
China is about to undergo a major reform of its securities offering and listing processes. Since the inception of China’s securities market in the early 1990s, the government has exercised tight control to determine which companies will be allowed to engage in initial public offerings and become listed on a national exchange. The system has led to both corruption and favoritism and has blocked numerable companies from access to capital markets. With the ascension in 2013 of Xi Jinping and Li Keqiang as the heads of the Chinese Communist Party and Premier, the government adopted reform of the market process as a major goal within its economic program. Under the proposal, the China Securities Regulatory Commission (CSRC) will no longer have major power over which companies can go public, what their offering prices will be or whether or where the issuer’s shares will be listed. According to the proposed bill, the CSRC’s role under the proposed reform has been substantially reduced. The authority to determine whether prospectus disclosure requirements have been met will principally move from the CSRC to the stock exchanges, which will also determine listing applications. The reform process, announced in November 2013, has been delayed as a result of China’s stock market crisis in July 2015. It now appears that the reform measures are back on track. Yet, despite a generally favorable attitude towards the reform, significant concerns exist among Chinese government officials and academics as to whether the open registration system will lead to a more efficient market. Unlike the United States, the Chinese securities markets are dominated by individual shareholders, many of whom are relatively inexperienced. Nor does China have the extensive infrastructure of experienced and trustworthy broker-dealers, investment advisors, and enforcement tools that exist in the U.S. Other than the principal reform proposal there are few specific regulations currently adopted to address concerns about market access and investor protection. This article examines the background leading to the reform proposal and analyzes whether and to what extent certain measures in the United States might be appropriate for adoption when the open registration system becomes reality.
Keywords: China; Securities law; IPO law; IPO